2019
DOI: 10.1186/s12870-019-2164-5
|View full text |Cite
|
Sign up to set email alerts
|

QTL identification for seed weight and size based on a high-density SLAF-seq genetic map in peanut (Arachis hypogaea L.)

Abstract: BackgroundThe cultivated peanut is an important oil and cash crop grown worldwide. To meet the growing demand for peanut production each year, genetic studies and enhanced selection efficiency are essential, including linkage mapping, genome-wide association study, bulked-segregant analysis and marker-assisted selection. Specific locus amplified fragment sequencing (SLAF-seq) is a powerful tool for high density genetic map (HDGM) construction and quantitative trait loci (QTLs) mapping. In this study, a HDGM wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 67 publications
5
60
1
1
Order By: Relevance
“…The deployment of the “Axiom_ Arachis ” array with 58,233 SNPs [ 25 ] in groundnut facilitated generation of high-throughput genotyping data for high-resolution trait mapping [ 45 ]. The studies also showed that SLAF-seq can help developing denser genetic map than GBS or SNP array [ 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The deployment of the “Axiom_ Arachis ” array with 58,233 SNPs [ 25 ] in groundnut facilitated generation of high-throughput genotyping data for high-resolution trait mapping [ 45 ]. The studies also showed that SLAF-seq can help developing denser genetic map than GBS or SNP array [ 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…All effects were defined as random to calculate the heritability rates. Broad sense heritability ( H 2 ) was estimated with the equation H 2 = σ g 2 /(σ g 2 + σ ge 2 + σ e 2 ), by the ANOVA analysis with QTL IciMapping v4.2 ( http://www.isbreeding.net/software/?type=detail&id=29 ) [ 46 ]. The σ g 2 , σ e 2 and σ ge 2 denoted the variances of genotypes (G), environment (E) and interaction of genotypes and environments (G x E).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies reported QTLs controlling pod/seed weight and size in peanut [12,[15][16][17][18][19][20][21][22][23][24][25][26]. However, a few of them involved crosses between wild and cultivated species.…”
Section: Introductionmentioning
confidence: 99%